5th International Conference on Biomedical Engineering in Vietnam - International Conference on the Development of Biomedical Engineering in Vietnam Ho Chi Minh City, Vietnam) 2014; Toi, Vo Van; Lien Phuong, Tran Ha; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This volume presents the proceedings of the Fifth International Conference on the Development of Biomedical Engineering in Vietnam which was held from June 16-18, 2014 in Ho Chi Minh City. The volume reflects the progress of Biomedical Engineering and discusses problems and solutions. I aims identifying new challenges, and shaping future directions for research in biomedical engineering fields including medical instrumentation, bioinformatics, biomechanics, medical imaging, drug delivery therapy, regenerative medicine and entrepreneurship in medical devices.
Electronic reproduction.
Keywords: Medical records -- Data processing; Biology -- Data processing; Biomedical engineering; Electronic books